Zika Virus Infects, Activates, and Crosses Brain Microvascular Endothelial Cells, without Barrier Disruption - Papa, Michelle P.; Meuren, Lana M.; Coelho, Sharton V. A.; Lucas, Carolina G. de Oliveira; Mustafá, Yasmin M.; Lemos Matassoli, Flavio; Silveira, Paola P.; Frost, Paula S.; Pezzuto, Paula; Ribeiro, Milene R.; Tanuri, Amilcar; Nogueira, Mauricio L.; et al. (Frontiers in Microbiology, 2017)
Zika virus (ZIKV) has been associated to central nervous system (CNS) harm, and virus was detected in the brain and cerebrospinal fluids of microcephaly and meningoencephalitis cases. However, the mechanism by which the virus reaches the CNS is unclear. Here, we addressed the effects of ZIKV replication in human brain microvascular endothelial cells (HBMECs), as an in vitro model of blood brain barrier (BBB), and evaluated virus extravasation and BBB integrity in a in vivo mouse experimental model. HBMECs were productively infected by African and Brazilian ZIKV strains (ZIKVMR766 and ZIKVPE243), which induce increased production of type I and type III IFN inflammatory cytokines and chemokines. Infection with ZIKVMR766 promoted earlier cellular death, in comparison to ZIKVPE243, but infection with either strain did not result in enhanced endothelial permeability. Despite the maintenance of endothelial integrity, infectious virus particles crossed the monolayer by endocytosis/exocytosis-dependent replication pathway or by transcytosis. Remarkably, both viruses’ strains infected IFNAR deficient mice, with high viral load being detected in the brains, without BBB disruption, which was only detected at later time points after infection. These data suggest that ZIKV infects and activates endothelial cells, and might reach the CNS through basolateral release, transcytosis or transinfection processes. These findings further improve the current knowledge regarding ZIKV dissemination pathways.